2022
DOI: 10.1371/journal.pone.0264987
|View full text |Cite
|
Sign up to set email alerts
|

The psychoactive effects of Bryophyllum pinnatum (Lam.) Oken leaves in young zebrafish

Abstract: Bryophyllum pinnatum (Lam.) Oken (BP) is a plant that is used worldwide to treat inflammation, infections, anxiety, restlessness, and sleep disorders. While it is known that BP leaves are rich in flavonoids, the extent of the beneficial and toxic effects of its crude extracts remains unclear. Although some neurobehavioral studies using leaf extracts have been conducted, none has examined the effects of water-extracted leaf samples. The zebrafish is a powerful animal model used to gain insights into the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
(96 reference statements)
2
7
0
Order By: Relevance
“…Again, this finding is one of the few, if not the first and only, reports on the antidepressant activity of B. pinnatum leaf extracts. The observed antidepressant activity of CEBP in this study may be related to a previous report of acute anxiolytic activity in young zebra fish [81]. T. catappa, T. dodoneifolius and B. pinnatum whose crude ethanol leaf extracts are investigated in this study, are widely used medicinal plants with efficacy in the traditional treatments of diverse disease spectrums.…”
Section: Discussionsupporting
confidence: 85%
“…Again, this finding is one of the few, if not the first and only, reports on the antidepressant activity of B. pinnatum leaf extracts. The observed antidepressant activity of CEBP in this study may be related to a previous report of acute anxiolytic activity in young zebra fish [81]. T. catappa, T. dodoneifolius and B. pinnatum whose crude ethanol leaf extracts are investigated in this study, are widely used medicinal plants with efficacy in the traditional treatments of diverse disease spectrums.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are in agreement with previous reports of similar anxiolytic, antidepressant and cognition-enhancing activities of T.dodoneifolius extracts [64] and anxiolytic activity of its congener T.globiferus extracts [65,66] in mice activity. They are also similar to previous reports of anxiolytic activity of B. pinnatum and its congener K. pinnata extracts in young zebrafish and rodents [40,84]. Anxiolytic activity reports on T. catappa were scanty but it has been reported to exhibit significant antidepressant effect in rodents subjected to chronic unpredictable stress [85].…”
Section: Effect Of Single Acute Doses Of Hydroalcoholic B Pinnatum T ...supporting
confidence: 90%
“…Previous studies have shown extracts of B. pinnatum and its congeners to exert dosedependent anticonvulsant activity, antidiabetic, anxiolytic, hypnotic and muscle relaxant effects in rodents [37][38][39], and antidiabetic and anxiolytic effects in young Zebra fish [40]. However, scientific reports on the anxiolytic activity of k. pinnata are scanty and this study, therefore, aims to investigate its acute anxiolytic effect in mice in the open field test.…”
Section: Plate 1 Bryophyllum Pinnatummentioning
confidence: 98%
“…Despite the growing number of studies describing pharmacological actions of Kalanchoe extracts, and the knowledge about flavonoids as important chemical constituents in this genus, most of the studies have just reported the presence of these molecules, without properly investigating their bioactive behavior. Indeed, several of these studies only suggest the potential role of flavonoids in a given activity [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], without assessing the isolated compound to confirm its bioactivity. The characterization of bioactive compounds is important not only to define the molecules responsible for a given biological property, but also for the development of phytomedicines.…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%